1996
DOI: 10.1159/000177096
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Echocardiography in 190 Patients with Chronic Congestive Heart Failure

Abstract: Survival in 190 consecutive patients with congestive heart failure, discharged from a general hospital, was studied. Sixteen patients were in New York Heart Association (NYHA) class I, 87 in II, 83 in III and 4 in IV. Median left ventricular ejection fraction (LVEF) from radionuclide ventriculography was 0.30 (range 0.06-0.74). Two-year survival was 68%. Wall motion index was the only echocardiographic variable with significant, independent, prognostic information on survival. The 2-year survival in NYHA class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 16 publications
0
4
1
2
Order By: Relevance
“…LVEF however, reflects global function and hypercontractile segments may offset hypokinetic segments thereby preserving overall LV systolic function. Some studies have reported that resting WMA is a more powerful predictor of outcome [17] whereas others report incremental prognostic information using both resting WMA and LVEF [18]. In our study, 53% with a resting WMA had an EF ≤ 50%, whereas 2% of patients with no resting WMA had an EF ≤ 50%.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…LVEF however, reflects global function and hypercontractile segments may offset hypokinetic segments thereby preserving overall LV systolic function. Some studies have reported that resting WMA is a more powerful predictor of outcome [17] whereas others report incremental prognostic information using both resting WMA and LVEF [18]. In our study, 53% with a resting WMA had an EF ≤ 50%, whereas 2% of patients with no resting WMA had an EF ≤ 50%.…”
Section: Discussioncontrasting
confidence: 44%
“…Regional left ventricular function provides additional prognostic information in patients post myocardial infarction [17, 23], and in patients with heart failure [18]. Although the presence of a resting WMA generally represents prior infarction, stunned or hibernating myocardium, it may also be found in individuals without coronary artery disease [13].…”
Section: Discussionmentioning
confidence: 99%
“…Endeavors to elucidate the disease processes that precede global ventricular dysfunction and its clinical implications have been undertaken mainly in patients with ischemic heart disease (3436) and heart failure (37). Among these selected symptomatic individuals, regional wall motion abnormalities identified by echocardiography have been shown to predict death and heart failure hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the LV global functional parameter LVEF is an important predictor of cardiac death in patients with DCM ( 2 , 17 ). The global and regional functions are closely related and the correlation between global systolic wall motion score measured by echocardiography (echocardiographic wall motion score index, WSMI) and LVEF obtained by radionuclide ventriculography is high ( r = 0.72) ( 40 , 41 ). Our present study showed a higher correlation between LVEF and SMS ( r = 0.917), possibly because both of the two parameters were obtained through gated SPECT MPI and were consistent.…”
Section: Discussionmentioning
confidence: 99%